2020
DOI: 10.1093/jalm/jfaa192
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Impact of Hormone Therapy on Laboratory Values in Transgender Patients over Time

Abstract: Background Known physiological changes occur while transgender patients are taking hormone therapy (HT). However, knowledge is limited about when laboratory values stabilize and if there are any long-term impacts, making it challenging for physicians to provide adequate gender-affirming care. We aim to analyze laboratory values with HT use over 5 years and after discontinuation of HT to define when values achieve stability. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…High-density lipoprotein (HDL) cholesterol decreased by 10.8% (95% CI −14.0 to −7.6). Similar results were reported by Liu et al (Taiwan) and Allen et al (Dallas, Texas) [93,94] with an increase in LDL cholesterol and a decrease in HDL cholesterol in trans men during the first year of testosterone therapy. Liu et al [93] examined the effects of 1 year of testosterone therapy in trans men (n = 65, mean age = 27.9) and found an increase in LDL cholesterol from 124.3 mg/dl to 131.3 mg/dl and a decrease in HDL cholesterol from 57.9 mg/dl to 52.8 mg/dl.…”
Section: Risk Factors For Trans Mensupporting
confidence: 89%
See 3 more Smart Citations
“…High-density lipoprotein (HDL) cholesterol decreased by 10.8% (95% CI −14.0 to −7.6). Similar results were reported by Liu et al (Taiwan) and Allen et al (Dallas, Texas) [93,94] with an increase in LDL cholesterol and a decrease in HDL cholesterol in trans men during the first year of testosterone therapy. Liu et al [93] examined the effects of 1 year of testosterone therapy in trans men (n = 65, mean age = 27.9) and found an increase in LDL cholesterol from 124.3 mg/dl to 131.3 mg/dl and a decrease in HDL cholesterol from 57.9 mg/dl to 52.8 mg/dl.…”
Section: Risk Factors For Trans Mensupporting
confidence: 89%
“…Along the same lines, Allen et al. [94] reported increases of hematocrit levels in trans men ( n = 91, mean age = 27.8) during testosterone treatment and decreases in trans women ( n = 126, mean age = 31.1) during estrogen treatment with or without an anti‐androgen, with no changes after 6 months of therapy when compared to measurements after 5 years of GAHT. A similar pattern was shown in 183 trans women and 119 trans men with follow‐up longer than 6 months [103].…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As in assessment of thrombotic risks, the effects of GAHT on lipid panels are difficult to summarize due to study and treatment heterogeneity. One study showed a decrease in LDL, HDL, and triglycerides, [27] whereas other studies have shown no significant difference, [28] an effect on HDL alone, [29] or a significant change in triglycerides alone. [5] Coadministration of progestins and anti-androgens may be the cause of some conflicting results, and more data are needed before conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 91%